Sequence Analysis of Six Blood Pressure Candidate Regions in 4,178 Individuals: The Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study - Morrison, Alanna C.; Bis, Joshua C.; Hwang, Shih-Jen; Ehret, Georg B.; Lumley, Thomas; Rice, Kenneth; Muzny, Donna; Gibbs, Richard A.; Boerwinkle, Eric; Psaty, Bruce M.; Chakravarti, Aravinda; Levy, Daniel (PloS one, 2014)
Genome-wide association studies (GWAS) identified multiple loci for blood pressure (BP) and hypertension. Six genes--ATP2B1, CACNB2, CYP17A1, JAG1, PLEKHA7, and SH2B3--were evaluated for sequence variation with large effects on systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), and mean arterial pressure (MAP). Targeted genomic sequence was determined in 4,178 European ancestry participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Common variants (≥50 minor allele copies) were evaluated individually and rare variants (minor allele frequency, MAF≤1%) were aggregated by locus. 464 common variants were identified across the 6 genes. An upstream CYP17A1 variant, rs11191416 (MAF = 0.09), was the most significant association for SBP (P = 0.0005); however the association was attenuated (P = 0.0469) after conditioning on the GWAS index single nucleotide polymorphism (SNP). A PLEKHA7 intronic variant was the strongest DBP association (rs12806040, MAF = 0.007, P = 0.0006) and was not in LD (r² = 0.01) with the GWAS SNP. A CACNB2 intronic SNP, rs1571787, was the most significant association with PP (MAF = 0.27, P = 0.0003), but was not independent from the GWAS SNP (r² = 0.34). Three variants (rs6163 and rs743572 in the CYP17A1 region and rs112467382 in PLEKHA7) were associated with BP traits (P<0.001). Rare variation, aggregately assessed in the 6 regions, was not significantly associated with BP measures. Six targeted gene regions, previously identified by GWAS, did not harbor novel variation with large effects on BP in this sample.